Environmental audit of industrial waste - Zahari, Muhammad Syaiful Annuruddin; Hasbullah, Mohd Hanif; Zulkafli, Nurul Farhana; Hassan, Hassan Hussein; Aden, Mohamed Ibrahim (Penerbit UTHM, 2020)
In this industrialization era, an environmental audit is become more complex which is a very strict action are needed in minimize a wastage. Employing an environmental management system is a significant undertaking but an extremely worthwhile one for any organisation. Certification has developed a step by step guide to aid companies in implementing the standard during their journey to ISO 14001 certification. This report discussed on manageable and unmanageable wastage in different companies. These activities give an impact also consequences to environment and lead to poor organization management.